An audit of sport nutrition services within male and female international rugby union: Implications for research and practice - Wilson, L.; Jones, B.; Backhouse, S. H.; Boyd, A.; Costello, N. (European Journal of Sport Science, 2025)
To critically evaluate sport nutrition services available to male and female international rugby unions. Fifteen participants, representing 16 international rugby unions, including nine female and seven male teams (one participant worked with both a female and male union), responded to an online survey. Twelve of the unions recruited were ranked in the top 10 globally by World Rugby. Twelve unions employed accredited nutrition practitioners with significant experience (> 5 years: n = 5; > 10 years: n = 4) and advanced qualifications (master's degrees: n = 8; doctorates: n = 2). Three unions did not employ a qualified nutrition practitioner (female: n = 2; male: n = 1). Full-time employment was more common among nutrition practitioners serving male (n = 4/5) versus female (n = 3/6) unions. Practitioners served male unions for more hours per week (42 ± 28) than female unions (24 ± 20). Practitioners were involved in sport science meetings (n = 14/15), anti-doping education, menu design, strategy development (n = 13/15), body composition assessments, individual consultations (n = 12/15), focusing on fuelling, recovery and injury rehabilitation (n = 14/15). Participants were "moderately confident" (n = 8/15) in using behaviour change techniques. Most participants agreed on the lack of female-specific nutrition guidance (n = 14/15), relying on guidance for male players due to limited evidence (n = 7/9). This study provides the first critical reflection of sport nutrition service delivery within international rugby. The findings highlight gender disparities for female players, with reduced applied support and a lack of female-specific guidelines. Recommendations include enhancing practitioner training in behaviour change, hiring qualified nutritionists, deemphasising body composition assessment, and conducting more research to improve nutrition services, especially for women.